Prevalence of myocarditis in pediatric intensive care unit cases presenting with other system involvement - Hanaa Ibrahim Rady; Hanan Zekri (Elsevier, 2015)
Objective: To assess children with myocarditis, the frequency of various presenting symptoms, and the accuracy of different investigations in the diagnosis. Methods: This was an observational study of 63 patients admitted to PICU with non-cardiac diagnosis. Cardiac enzymes, chest-X ray, echocardiography, and electrocardiogram were performed to diagnose myocarditis among those patients. Results: There were 16 cases of definite myocarditis. The age distribution was non-normal, with median of 5.5 months (3.25-21). Of the 16 patients who were diagnosed with myocarditis, 62.5% were originally diagnosed as having respiratory problems, and there were more females than males. Among the present cases, the accuracy of cardiac enzymes (cardiac troponin T [cTn] and creatine phosphokinase MB [CKMB]) in the diagnosis of myocarditis was only 63.5%, while the accuracy of low fractional shortening and of chest-X ray cardiomegaly was 85.7 and 80.9%; respectively. Cardiac troponin folds 2.02 had positive predictive value of 100%, negative predictive value of 88.7%, specificity of 100%, sensitivity of 62.5%, and accuracy of 90.5%. Conclusions: Children with myocarditis present with symptoms that can be mistaken for other types of illnesses. When clinical suspicion of myocarditis exists, chest-X ray and echocardiography are sufficient as screening tests. Cardiac troponins confirm the diagnosis in screened cases, with specificity of 100%. Resumo: Objetivo: Determinar as crianças com miocardite, a frequência de vários sintomas apresentados e a precisão de diferentes investigações no diagnóstico. Métodos: Estudo observacional de 63 pacientes internados na UTIP com diagnóstico de problemas não cardíacos. Os exames de enzimas cardíacas, raio-X do tórax, ecocardiograma e eletrocardiograma (ECG) foram realizados para diagnosticar miocardite dentre os pacientes. Resultados: Houve 16 casos de miocardite definida. A distribuição etária não foi normal, com média de 5,5 meses (3,25-21). Dos 16 pacientes diagnosticados com miocardite, 62,5% foram originalmente diagnosticados como com problemas respiratórios, e a mulheres estavam em maior número que os homens. Dentre nossos casos, a precisão das enzimas cardíacas (cTn e CKMB) no diagnóstico da miocardite foi de apenas 63,5%, apesar de a precisão da baixa fração de encurtamento (FS) e do raio-X de tórax revelando cardiomegalia ter sido 85,7% e 80,9%; respectivamente. A Troponina Cardíaca em 2,02 vezes apresentou valor preditivo positivo = 100%, valor preditivo negativo = 88,7%, especificidade = 100%, sensibilidade = 62,5% e precisão = 90,5%. Conclusões: As crianças com miocardite apresentam sintomas que podem ser confundidos com outros tipos de doenças. Quando há suspeita clínica de miocardite, raio-X de tórax e ecocardiografia são testes de rastreamento suficientes. As Troponinas Cardíacas confirmam o diagnóstico em casos examinados, com especificidade de 100%. Keywords: Myocarditis, Cardiac enzymes, Troponin, Children, Pediatric intensive care unit, Palavras-chave: Miocardite, Enzimas cardíacas, Troponina, Crianças, Unidade de terapia intensiva pediátrica